Hubungan antara Peran Teman Sebaya dengan Perilaku Perundungan pada Peserta Didik SMP Negeri 1 Tondano - Mamahit, Brenda; Adam, Hilman; Wowor, Ribka Elisabeth (Yayasan Bina Lentera Insan, 2026)
Bullying remains a serious problem among school-aged adolescents. Based on the Global School-Based Student Health Survey (GSHS) by the World Health Organization, bullying is measured by the percentage of students who reported experiencing bullying at least once in the past 30 days (WHO, 2025). Globally, 41% of schoolchildren in Indonesia reported experiencing bullying in various forms (UNICEF, 2020), while the Indonesian Child Protection Commission (KPAI) showed a significant increase in bullying cases in education in 2024. Peers play a role in shaping bullying behavior; the stronger the influence of the peer group, the higher the bullying behavior (Sari and Budiman, 2021). On the other hand, a literature review by Sitanggang et., al (2025) showed a negative relationship between the role of peers and bullying behavior; the higher the role of peers, the lower the bullying behavior in students. The purpose of this study was to analyze the relationship between the role of peers and bullying behavior in students at SMP Negeri 1 Tondano. The study was conducted at SMP Negeri 1 Tondano, and a sample of 100 students using stratified random sampling. The research instrument used the Peer Relationship Scale (PRS) and the Olweus Bully/Victim Questionnaire (OBVQ-R). Univariate analysis used the Spearman Rank Test using the SPSS ver.25 application. The results showed that 80.0% of the peer role was high. The results of the bivariate analysis obtained p <0.020 with an R value of -0.233, indicating a significant relationship with low correlation strength and a negative correlation between the role of peers and bullying behavior in students of SMP Negeri 1 Tondano.